Faktor–faktor yang mempengaruhi inflasi Provinsi-Provinsi di Sumatera - Lailan Syafrina Hasibuan; Rahma Nurjanah; Etik Umiyati (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
This study aims to: 1) analyze inflationary developments, road infrastructure, government spending, provincial minimum wage, and economic growth provincial in Sumatra; 2) analyze the influence of road infrastructure, government spending, provincial minimum wage, and economic growth provincial in Sumatra. This research uses a descriptive analysis method to determine the development of each research variable and quantitative methods using panel data regression approach random effect. Based on the descriptive analysis of inflationary development, road infrastructure stagnated, government spending, provincial minimum wage, and economic growth was increased every year. The regression of panel data with random effect approach variable of the provincial minimum wage has a positive and significant influence on the inflation of provincial in Sumatra. While road infrastructure, government spending, economic growth have no significant effect on provincial inflation in Sumatra. Keywords: Inflation, Government spending, Economic growth.